Brunch: A History - Ternikar, Farha Bano (Rowman & Littlefield Publishers, 2014)
When Americans think of brunch, they typically think of Sunday mornings swelling into early afternoons; mimosas and bloody Marys; eggs Benedict and coffee cake; bacon and bagels; family and friends. This book presents a modern history of brunch not only as a meal, but also as a cultural experience. Relying on diverse sources, from historic cookbooks to Twitter and television, Brunch: A History is a global and social history of the meal including brunch in the United States, Western Europe, South Asia and the Middle-East. Brunch takes us on a tour of a modern meal around the world. While brunch has become a modern meal of leisure, its history is far from restful; this meal’s past is both lively and fraught with tension. Here, Farha Ternikar explores the gendered and class-based conflicts around this meal, and provides readers with an enlightening glimpse into the dining rooms, verandas, and kitchens where brunches were prepared, served, and enjoyed.